Assessing Airway Patency And Breathing In NBC Category 4R - The RG Method. Issue 3 (1st January 2006) - Tong, JL; Taylor, A; House, J; Smith, JE
Abstract : Introduction: Confirming airway patency and the presence of breathing has significant limitations when both the casualty and medical personnel are in NBC category 4R. In casualties with limited signs of breathing, IPE may adversely affect the efficiency of clinical assessment, and when the triage sieve is used this could result in the misdiagnosis of death. This manuscript describes and evaluates the Respirator-Glove (RG) method, of assessing airway patency and breathing in NBC category 4R. Methods: Amedical examination glove was fitted over the primary speech module of the S10 NBC respirator of a volunteer casualty dressed in 4R. Two groups were studied; the first used an intact glove the second used a glove minus one finger. Breathing patterns A, B and C, representing normal breathing, hypoventilation and apnoea respectively, were randomly performed by the casualty for 15 seconds. A blinded observer recorded the glove inflation and movement and using these signs determined if breathing was present. Results: All of the randomly performed breathing pattern simulations were correctly identified in both groups, with glove inflation only occurring during exhalation. In the perforated glove group, the large expiratory air leak through the hole limited the development of continuous positive airway pressure and the respirator seal wasmaintained. In the non-perforated glove group the respirator seal was compromised. No difficulty was encountered attaching the gloves to the respirator speech module. Discussion: As an aid to clinical examination, the Respirator-Glove (RG) method provides a reproducible visual assessment of airway patency and spontaneous ventilation in unconscious 4R casualties. It can be utilised at any point in the evacuation chain, may improve the identification of T1 casualties and could reduce the risk of death being misdiagnosed. The efficiency of clinical assessment in 4R will improve by introducing the RG method into CBRN medical training programmes.